Sex disparities in the risk of intracranial aneurysm rupture: a case–control study - Shen, Dong; Cai, Miaochun; Luo, Yi; Li, Zhihao; Zhang, Peidong; Wang, Yongkang; Fan, Wenlong; Wu, Hanqiu; Yu, Yezhou; Gong, Xijun; Mao, Chen (Frontiers in Neurology, 2024)
BackgroundThere are sex disparities in the risk of ruptured intracranial aneurysm (IA), but which sex-specific factors are related to ruptured IA remains inconclusive.MethodsData from electronic medical records from two tertiary hospitals, collected between January 2012 and December 2019, were analyzed for this study. All IAs were confirmed by computed tomographic angiography or digital subtraction angiography. Sex-specific factors associated with ruptured IA were analyzed using multivariable logistic models with a case–control study design. Age, aneurysm size, and aneurysm location subgroup analyses were conducted according to sex.ResultsIn total, 1883 patients [1,117 (59.32%) female, 766 (40.68%) male] with 2,423 IAs were included; 734 (38.98%) of patients had ruptured IAs. Compared with males, females had a higher risk of ruptured IA [odds ratio, 1.72 (95% confidence interval, 1.38–2.14)]. Age, aneurysm location, aneurysm size, multiple aneurysms, hypertension, history of intracerebral hemorrhage, and ischemic stroke were associated with risk of IA rupture in both sexes. In the subgroups based on the covariates used in this study, we only identified statistically significant interaction between sex and age. Although ruptured IAs were most common in males and females aged 50–59 and 60–69 years, respectively, risk of IA rupture peaked at ages 30 and 30–50 years in females and males, respectively, and decreased with age in both sexes.ConclusionFemales have an overall greater IA incidence and higher risk of IA rupture than males. Young age is one sex-specific risk factor associated with ruptured IA which could related to potential influence of hypertension, which might suggest more attention of IA rupture prevention in younger female.